Wound Field Synchronous Motor Design for Electric Vehicles - Demirdag, Mehmet; Partal, Sibel Zorlu (IEEE, 2025)
In this study, a wound-field synchronous motor (WFSM) is proposed as an alternative to permanent magnet synchronous motors (PMSMs) for electric vehicle applications, aiming to address key drawbacks associated with PMSMs, such as high material costs, supply limitations, and environmental concerns. To this end, an interior permanent magnet synchronous motor was initially selected as a reference model and subjected to detailed electromagnetic analysis using ANSYS Maxwell. Subsequently, while retaining the stator geometry of the reference design, a wound-field rotor configuration was developed to replace the permanent magnet rotor. The redesigned WFSM was then analyzed under the same simulation conditions. Key performance indicators, including phase currents, torque output, and efficiency maps, were computed through finite element analysis. In conclusion, both motors were comparatively evaluated in terms of efficiency, torque capacity, overall mass, cost, and other critical design parameters, and the results were analyzed.
Keywords: magnet free; wound field synchronous motor; ANSYS Maxwell; Delta shape PMSM; electrical vehicle motor design; Energy & Fuels; Engineering; Telecommunications